2018
DOI: 10.26444/aaem/79810
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chlorinated water on the development of allergic diseases – An overview

Abstract: Indoor swimming pools can be used all year round and serve for one of the most popular sport pursued for recreation The positive effect of swimming arises in particular from the involvement of all the muscles of the body, decreasing the burden on the joints, as well as functional improvement of both the lungs and heart. Chlorine is typically used to disinfect swimming pool water and as a result the changes that take place lead to the formation of by-products, such as monochloramines (NH 2 Cl), dichloramines (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…In the textile industry, chlorine is the main substance in the bleaching process. In the textile industry, chlorine is the main substance in the bleaching process, but can cause inflammation of the nasal and respiratory tract mucosal [10]. Previous studies reported the occurrence of lesions in the olfactory nerve in the form of redistribution of [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…In the textile industry, chlorine is the main substance in the bleaching process. In the textile industry, chlorine is the main substance in the bleaching process, but can cause inflammation of the nasal and respiratory tract mucosal [10]. Previous studies reported the occurrence of lesions in the olfactory nerve in the form of redistribution of [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…Studies based on serum pneumoproteins show that not only acute but also chronic exposure to NCl 3 can increase the lung epithelium permeability and thereby perhaps facilitate the transepithelial delivery of allergens to dendritic cells 46 and contribute to a T2-dependent immune response. 61,62 Recent experimental evidence in mice has shown that chronic chlorine inhalation contributes to exacerbate airways inflammation in asthma by mobilizing pro-inflammatory macrophages into the lung as well as stimulating group 2 and 3 ILCs. 63 The barrier disruption effect may occur also on the dermal layer.…”
Section: Effec Ts Of Chroni C E Xp Osure Smentioning
confidence: 99%
“…The calibrated model shows high dose chlorine injection in the DWTP and how chlorine behaves along with the network (Figure 4). Chlorine might cause organoleptic discomfort to the population near this point because of the smell and the taste; according to a study from Bangladesh, the chlorine taste in tap water was acceptable up to 1.25 mg/L FRC and they were willing to drink because of the safety perception under 2.0 mg/L FRC [65,66]. Initial conditions have a mean deviation for FRC in the last 24 h of 0.042 mg/L and a DEL = 340.29 mg/L, using CBS after the node RDTOT29 with a dosage of 14,462 g/d.…”
Section: Case Studymentioning
confidence: 99%